The Black Hole at the Center of the Psalms - Strawn, Brent A. (Interpretation, 2024)
This essay explores the motif of "the Pit" as a third, thematic focus for the Psalter (alongside "refuge" and "pathway"). Especially as it comes to fullest expression in Psalm 88, the Pit can be seen as the "black hole" at the center of the Psalms. Yet, while powerful, Psalm 88, and the presence of the Pit therein, does not have the final word. The sequence of the following psalms (Psalms 89, 90, and 91) slowly but surely draws the poet of Psalm 88 out of what has been called the saddest of all psalms. In this way, Psalm 88 retains its witness within the Psalter, but it is also not alone within the Psalms. Astrophysics has determined that black holes are not only destructive; they are also generative, shaping things around them and producing massive amounts of energy. In this light, the Pit, too, can be viewed as a generative theme for the Psalms, one that is crucial—somehow even central—but, in the end, transcended.